Evaluation of a fibrate, specific stimulant of PPARα, as a therapeutic alternative to the treatment of clinical ovine pregnancy toxaemia. Issue 5 (11th March 2016) - Da Silva, S.; Cal‐Pereyra, L. G.; Benech, A.; Acosta‐Dibarrat, J.; Martin, M. J.; Abreu, M. C.; Perini, S.; González‐Montaña, J. R.
Abstract : Ovine pregnancy toxaemia is a metabolic disorder affecting sheep in their last 6 weeks of pregnancy as a result of their inability to maintain adequate energy homoeostasis. Different alternative treatments are available with variable results. The aim of this research was to evaluate a peroxisome proliferator‐activated receptor alpha (PPARα) stimulant as an alternative to treat clinical pregnancy toxaemia. Thirty‐three adult sheep, with known gestation date and carrying a single foetus, were fasted from day 130 of gestation until animals showed clinical disease. From that moment onwards, sheep were treated during 6 days with three different therapeutic alternatives: 10 mg/kg of 2‐methyl‐2‐phenoxy‐propionic acid; 10 mg/kg of 2‐methyl‐2‐phenoxy‐propionic acid + 100 mL of propylene glycol oral; or 100 mL of propylene glycol oral. Glycaemia and serum β‐hydroxybutyrate (BHOB) were determined daily. Liver biopsies were taken at day 130 of gestation, at the beginning and end of treatments and at 5 days postpartum, evaluating the extent and degree of the steatosis lesion. Even though in sheep treated with 2‐methyl‐2‐phenoxy‐propionic acid, serum concentrations of glucose and BHOB recovered more slowly, we conclude that 2‐methyl‐2‐phenoxy‐propionic acid alone or combined with propylene glycol can be used as an alternative to effectively treat fatty liver, and therefore pregnancy toxaemia.